Integrative analysis of different low-light-tolerant cucumber lines in response to low-light stress - Li, Dandan; Yu, Fushun; Zhang, Yanzhao; Hu, Kaihong; Dai, Dongyang; Song, Siwen; Zhang, Fan; Sa, Rina; Lian, Hua; Sheng, Yunyan (Frontiers in Plant Science, 2023)
Introduction Low light stress inhibits plant growth due to a line of physiological disruptions in plants, and is one of the major barriers to protected cucumber cultivation in northern China. Methods To comprehensively understand the responses of cucumber seedlings to low-light stress, the low-light-tolerant line (M67) and The low-light-sensitive line (M14) were conducted for the analysis of photosynthetic phenotype, RNA sequencing (RNA-seq) and the expression level of photosynthesis-related genes in leaves under low-light stress and normal light condition (control). Results The results showed that there was a sharp decrease in the photosynthate accumulation in the leaves of the sensitive line, M14, resulting in a large decrease in the photosynthetic rate (Pn) (with 31.99%) of leaves compared to that of the control, which may have been caused by damage to chloroplast ultrastructure or a decrease in chlorophyll (Chl) content. However, under the same low-light treatment, there was no large drop in the photosynthate accumulation and even no decrease in Pn and Chl content for the tolerant line, M67. Moreover, results of gene expression analysis showed that the expression level of genes CsPsbQ (the photosystem II oxygen-evolving enhancer protein 3 gene) and Csgamma (ATPase, F1 complex gene) in the M14 leaves decreased sharply (by 35.04% and 30.58%, respectively) compared with the levels in the M67 leaves, which decreased by 14.78% and 23.61%, respectively. The expression levels of genes involved in Chl synthesis and carbohydrate biosynthesis in the leaves of M14 decreased markedly after low-light treatment; in contrast, there were no sharp decreases or changes in leaves of M67. Discussion Over all, the ability of cucumber to respond to low-light stress, as determined on the basis of the degree of damage in leaf structure and chloroplast ultrastructure, which corresponded to decreased gene expression levels and ATP phosphorylase activity, significantly differed between different low-light-tolerant lines, which was manifested as significant differences in photosynthetic capacity between them. Results of this study will be a reference for comprehensive insight into the physiological mechanism involved in the low-light tolerance of cucumber.